Brincidofovir clearance of acyclovir‐resistant herpes simplex virus‐1 and adenovirus infection after stem cell transplantation. Issue 5 (16th September 2016) - Voigt, S.; Hofmann, J.; Edelmann, A.; Sauerbrei, A.; Kühl, J.‐S.
Abstract: Infections with adenovirus (AdV) and herpesviruses can result in considerable morbidity and mortality in pediatric hematopoietic stem cell transplant (SCT) recipients. Herpes simplex virus (HSV) reactivations are usually prevented by acyclovir (ACV) prophylaxis, whereas cidofovir (CDV) has been used off indication to manage AdV infections. We report a child with myelodysplastic syndrome undergoing multiple SCT, who experienced HSV‐1 disease including severe mucositis and herpetic whitlow, as well as high viral load AdV DNAemia. Both ACV and CDV were ineffective; however, viral loads were decreased with brincidofovir, resulting in viral clearance. A subsequent Epstein–Barr virus disease with relevant meningoencephalitis responded to rituximab.